Synthesis and Characterization of bis(N,N-Diethylnicotinamide) p-Halogenobenzoate Complexes of Co(II) - F. OZTURKKAN, ELIF; ALI KOSE, DURSUN; NECEFOGLU, HACALI; UZUN, IBRAHIM (Asian Journal of Chemistry, 2010)
Halogenobenzoates are commonly applied in industrial and medical fields. Four novel mixed ligand complexes of Co(II) with p-florobenzoate, p-chlorobenzoate, p-bromobenzoate, p-iodobenzoate and N,N-diethylnicotinamide were synthesized and characterized on the basis of elemental analysis, FT-IR spectroscopic study, solid state UV-Vis spectrometric and magnetic susceptibility data. The thermal behaviour of the complexes was studied by simultaneous TG-DTA methods in static air atmosphere and the mass spectra data are recorded. According to the microanlytical results, formulae of complexes are C34H36N4O8FCo, C34H36N4O8ClCo, C34H36N4O8BrCo and C34H36N4O8ICo. The complexes contain two mole of coordination waters, two mole of p-halogenobenzoate and two mole of N,Ndiethylnicotinamide (dena) ligands per formula unit. In these complexes, the p-halogenobenzoate and N,N-diethylnicotin-amide behave as monodentate ligand through acidic oxygen and nitrogen of pyridine ring. The decomposition pathways and the stability of the complexes are interpreted in the terms of the structural data. The final decomposition products were found to be the CoO.